Clinical reappraisal of SHORT syndrome with PIK3R1 mutations: toward recommendation for molecular testing and management - Avila, Magali; Moog, Ute (Clinical genetics, 2016)
SHORT syndrome has historically been defined by its acronym: short stature (S), hyperextensibility of joints and/or inguinal hernia (H), ocular depression (O), Rieger abnormality (R) and teething delay (T). More recently several research groups have identified PIK3R1 mutations as responsible for SHORT syndrome. Knowledge of the molecular etiology of SHORT syndrome has permitted a reassessment of the clinical phenotype. The detailed phenotypes of 32 individuals with SHORT syndrome and PIK3R1 mutation, including eight newly ascertained individuals, were studied to fully define the syndrome and the indications for PIK3R1 testing. The major features described in the SHORT acronym were not universally seen and only half (52%) had four or more of the classic features. The commonly observed clinical features of SHORT syndrome seen in the cohort included intrauterine growth restriction (IUGR) <10th percentile, postnatal growth restriction, lipoatrophy and the characteristic facial gestalt. Anterior chamber defects and insulin resistance or diabetes were also observed but were not as prevalent. The less specific, or minor features of SHORT syndrome include teething delay, thin wrinkled skin, speech delay, sensorineural deafness, hyperextensibility of joints and inguinal hernia. Given the high risk of diabetes mellitus, regular monitoring of glucose metabolism is warranted. An echocardiogram, ophthalmological and hearing assessments are also recommended.
First published: 24 October 2015
Gesehen am 11.02.2020